Equine infectious anemia virus in naturally infected horses from the Brazilian Pantanal - Cursino, Andreia Elisa; Vilela, Ana Paula Pessoa; Franco-Luiz, Ana Paula Moreira; de Oliveira, Jaquelline Germano; Nogueira, Márcia Furlan; Júnior, João Pessoa Araújo [UNESP]; de Aguiar, Daniel Moura; Kroon, Erna Geessien (Springer Nature, 2018)
Equine infectious anemia (EIA) has a worldwide distribution, and is widespread in Brazil. The Brazilian Pantanal presents with high prevalence comprising equine performance and indirectly the livestock industry, since the horses are used for cattle management. Although EIA is routinely diagnosed by the agar gel immunodiffusion test (AGID), this serological assay has some limitations, so PCR-based detection methods have the potential to overcome these limitations and act as complementary tests to those currently used. Considering the limited number of equine infectious anemia virus (EIAV) sequences which are available in public databases and the great genome variability, studies of EIAV detection and characterization molecular remain important. In this study we detected EIAV proviral DNA from 23 peripheral blood mononuclear cell (PBMCs) samples of naturally infected horses from Brazilian Pantanal using a semi-nested-PCR (sn-PCR). The serological profile of the animals was also evaluated by AGID and ELISA for gp90 and p26. Furthermore, the EIAV PCR amplified DNA was sequenced and phylogenetically analyzed. Here we describe the first EIAV sequences of the 5’ LTR of the tat gene in naturally infected horses from Brazil, which presented with 91% similarity to EIAV reference sequences. The Brazilian EIAV sequences also presented variable nucleotide similarities among themselves, ranging from 93,5% to 100%. Phylogenetic analysis showed that Brazilian EIAV sequences grouped in a separate clade relative to other reference sequences. Thus this molecular detection and characterization may provide information about EIAV circulation in Brazilian territories and improve phylogenetic inferences.